Lecturer Quality and Academic Workload in the Era of Digital Transformation: A Systematic Literature Review - Efrita Norman; Enah Pahlawati; Adrian Adha; Ahmad Juhari (MES Management Journal, 2026)
Higher education institutions are under increasing pressure to maintain lecturer quality while responding to expanding academic workload, digital transformation, and institutional performance demands. This systematic literature review aims to synthesize evidence on how academic workload and digital transformation shape lecturer quality within the framework of higher education human resource development. The review focuses on lecturers, faculty members, academic staff, and university educators in the context of teaching, research, assessment, digital adaptation, well-being, job satisfaction, and institutional support.This study employed a systematic literature review design using Scopus as the main database. The search strategy applied Boolean combinations related to lecturer quality, academic workload, digital transformation, and higher education. The screening process followed PRISMA logic, beginning with 475 identified records and resulting in 35 studies included in the final thematic synthesis. Data were extracted and coded according to workload dimensions, digital transformation aspects, well-being indicators, institutional support, and lecturer quality outcomes. The review generated three major findings. First, academic workload intensification is a key determinant of lecturer quality because lecturer work now includes teaching, research, publication, assessment, administration, mentoring, and institutional service. Excessive or poorly distributed workload may weaken teaching effectiveness, publication productivity, professional identity, and sustainable academic engagement. Second, digital transformation has a dual role. It can reduce workload through automation, digital assessment, online platforms, and workload planning tools, but it can also intensify work through digital preparation, technostress, artificial intelligence-related academic integrity challenges, and continuous adaptation. Third, lecturer well-being, job satisfaction, and institutional support function as important mechanisms linking workload and digital change to sustainable lecturer performance. This review concludes that lecturer quality should be understood as a sustainable human resource development outcome rather than merely an individual competence indicator. Higher education institutions need fair workload governance, digital competence development, mentoring, technical support, research support, and well-being-oriented academic management to sustain lecturer quality in the digital era.